KEPEMIMPINAN SITUASIONAL UNTUK MENINGKATKAN DAYA SAING LUARAN PENDIDIKAN ABAD 21 - Vivi Nindiantika; Nurul Ulfatin; Juharyanto Juharyanto (Universitas Negeri Malang, 2019)
Abstrack: The purpose of this research was to describe the situational leadership to improve the external competitiveness of the education of the 21st century. This study used a qualitative approach. The data collected by the method of interview, observation, and documentation. The result of the research was (1) the external competitiveness of the educational Profile of the 21st century the intended Junior Hight School Brawijaya Smart School there are three components, among others, character, competence, and insight; (2) situational leadership Behavior to improve the external competitiveness of the education of the 21st century through the orientation of the vision, mission, and goals, as well as through programs that are made; (3) leadership in the circumstantial conditioning to improve the external competitiveness of 21st century education is done through conditioning affect teachers, educational personnel in influencing conditioning, conditioning affect carers his pupil, and conditioning in affect learners. Keywords: situational leadership, education output of 21st century Abstrak: Tujuan penelitian ini untuk mendeskripsikan kepemimpinan situasional untuk meningkatkan daya saing luaran pendidikan abad 21. Penelitian ini menggunakan pendekatan kualitatif. Data dikumpulkan dengan metode wawancara, observasi, dan dokumentasi. Hasil penelitian adalah: (1) Profil daya saing luaran pendidikan abad 21 yang dituju SMP Brawijaya Smart School yaitu terdapat tiga komponen antara lain karakter, kompetensi, dan wawasan; (2) Perilaku kepemimpinan situasional untuk meningkatkan daya saing luaran pendidikan abad 21 yaitu melalui orientasi visi, misi, dan tujuan, serta melalui program yang dibuat; (3) Pengondisian dalam kepemimpinan situasional untuk meningkatkan daya saing luaran pendidikan abad 21 dilakukan melalui pengondisian dalam mempengaruhi guru, pengondisian dalam mempengaruhi tenaga kependidikan, pengondisian dalam mempengaruhi wali murid, dan pengondisian dalam mempengaruhi peserta didik. Kata Kunci: kepemimpinan situasional, luaran pendidikan abad 21